Penciptaan Karya Tari Layantara: Representasi Interaksi Sosial yang Terputus dalam Era Digital - Rahmat Fajar Ramadhan; Wardi Metro; Idun Ariastuti; Dony Osmond (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Layantara is a dance work that represents the social phenomenon of increasingly fragmented human interaction due to the pervasive influence of digital technology. The creation is driven by concerns over how human connections are gradually replaced by virtual relationships that are passive, shallow, and disconnected from physical presence. This work focuses on the experience of individuals who appear connected digitally, yet remain emotionally and socially distant. The choreography adopts a symbolic approach using transparent plastic as a metaphor for the thin but impenetrable boundaries that separate individuals from genuine interaction. The three-part structure of the piece interprets layers of interaction: beginning with passive contact, moving through disorientation and distancing, and culminating in an intense physical effort to reconnect, revealing the illusion within digital proximity. Layantara invites the audience into a reflective space, encouraging awareness and critical thought regarding the forms of connection that shape modern life, and the essential value of physical presence in social relationships.